Asia-Pacific perspectives on international humanitarian law / edited by Suzannah Linton, Tim McCormack, Sandesh Sivakumaran. - Linton, Suzannah; McCormack, Tim; Sivakumaran, Sandesh (Cambridge University Press, 2020)
Place is inextricably linked to history by way of culture, language, philosophy, faith and the development of worldviews. The richness and depth of experience of the Asia-Pacific region has been under-studied, over-simplified and under-appreciated. This book addresses that lacuna in the subject area of international humanitarian law. Drawing on authoritative perspectives and interviews with experts in and on this topic, including four of the region's most distinguished international judges, forty-one chapters thematically examine the development of international humanitarian law; practice and application of international humanitarian law; implementation and enforcement of international humanitarian law; and looking to the future and enhancing compliance with international humanitarian law. The expert contributors draw out unique features, providing fresh insights to scholarship. Contributions on and from the area also grapple with the regional commitments to humanitarianism generally, illuminating how and why international humanitarian law might be more readily accepted or ignored in armed conflicts in the region.